Protection of Hajj and Umrah Pilgrims from Fraud: Evidence from Indonesia - Setiawan, Nanang; Soewarno, Noorlailie (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2024)
This study explores the prevalence of fraud targeting Hajj and Umrah pilgrims in Indonesia and examines the government's role in protecting these pilgrims. Utilizing a qualitative approach, data were collected through observations and interviews with key stakeholders, including officials from the Ministry of Religious Affairs (MoRA), travel agency representatives, and Umrah pilgrims in an East Java district. The findings reveal that excessive trust in Hajj and Umrah travel agencies without verifying their licenses and track records is the primary cause of fraud. Additionally, Ponzi schemes by certain travel agencies, offering low-cost Umrah packages with uncertain travel schedules, further exacerbate the issue. The government's